Design and performance analysis of a slotted blade impeller for electrical submersible pumps - Wei Cui; Ziming Feng; Yuqiao Zhao; Wenzheng Chen; Xiangyu Song (Results in Engineering, 2025)
To resolve gas locking and head deterioration in traditional centrifugal submersible pumps handling fluids with Gas Volume Fraction (GVF) >10 %, this study designs a novel slotted blade impeller using orthogonal experiments (four factors/four levels) and Computational Fluid Dynamics technology. Key parameters—slot position (R), width (b), deflection angle (β), and depth (h)—were optimized, revealing β = 60° as the dominant factor (priority: β > b > R > h). The optimal single-slot configuration (R = 29 mm, b = 2 mm, β = 60°, h = 0.75) achieved 2.575 m head and 23.398 % efficiency at GVF=30 %, while reducing high-GVF zones (GVF>80 %) to 3.757 % flow volume. A breakthrough double-slot design (Slot 1: R = 29 mm, b = 2 mm; Slot 2: R = 24 mm, b = 1 mm) further enhanced performance to 2.644 m head, 23.838 % efficiency, and 1.067 % gas volume, by fragmenting gas accumulation and enabling dispersed bubble flow via stepwise pressurization. This slotted impeller eliminates gas locking at Gas Volume Fractions (GVFs) >10 %, providing a field-deployable solution for stable high-GVF oil well production without external separators.